2020
DOI: 10.1101/2020.10.26.353300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remdesivir Metabolite GS-441524 Effectively Inhibits SARS-CoV-2 Infection in Mice Models

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) rapidly spreads across worldwide and becomes a global pandemic. Remdesivir is the only COVID-19 treatment approved by U.S. Food and Drug Administration (FDA); however, its effectiveness is still under questioning as raised by the results of a large WHO Solidarity Trial. Herein, we report that the parent nucleotide of remdesivir, GS-441524, potently inhibits the replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Vero E6 and other ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…As such, the ester hydrolysis and the metabolism from alanine metabolite to MP-Nuc are the most essential steps for ProTide activation. However, recent findings showed that compared with remdesivir, GS-441524 had a stronger anti-SARS-CoV-2 efficacy in Vero E6 cells but a weaker efficacy in Calu-3 5 , 66 and Caco-2 cells. 5 , 66 Whether GS-441524 or isopropyl-GS-441524 can be more effective for COVID-19 treatment than remdesivir warrants further in vivo investigations.…”
Section: Discussionmentioning
confidence: 97%
“…As such, the ester hydrolysis and the metabolism from alanine metabolite to MP-Nuc are the most essential steps for ProTide activation. However, recent findings showed that compared with remdesivir, GS-441524 had a stronger anti-SARS-CoV-2 efficacy in Vero E6 cells but a weaker efficacy in Calu-3 5 , 66 and Caco-2 cells. 5 , 66 Whether GS-441524 or isopropyl-GS-441524 can be more effective for COVID-19 treatment than remdesivir warrants further in vivo investigations.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has a challenging pharmacological profile allowing intravenous administration only [39][40][41] . We demonstrate that the parent nucleoside GS-441524 [12][13][14][15][16] can "sterilize" H(s)AEC cultures from SARS-CoV2 as no rebound of the virus was noted several days after removal of the molecule. Differences in antiviral potencies of RDV and GS-441524 have been reported depending on the cell lines used, which correlates with the formation of the biologically active (5'-triphosphate) metabolite 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that the parent nucleoside GS-441524 [12][13][14][15][16] can "sterilize" H(s)AEC cultures from SARS-CoV2 as no rebound of the virus was noted several days after removal of the molecule. Differences in antiviral potencies of RDV and GS-441524 have been reported depending on the cell lines used, which correlates with the formation of the biologically active (5'-triphosphate) metabolite 12,13 . Data from a pharmacokinetic study in mice suggests that GS-441524 could possibly be considered as an oral drug 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat pharmacokinetics study, it showed a good plasma distribution and a long half-life (t 1/2 = 4.8 h). Considering that GS-441524 is the main metabolite of remdesivir in plasma, it is speculated that GS-441524 contributes to the anti-COVID-19 effect of remdesivir [ 22 ]. GS-441524 may become a promising cheap drug candidate for the treatment of COVID-19 and future emerging CoV diseases.…”
Section: Rdrp Inhibitorsmentioning
confidence: 99%